Opłaty za udostępnienie informacji publicznej do ponownego wykorzystania - Piskorz-Ryń, Agnieszka (Kwartalnik Prawa Publicznego, 2012)
The purpose of this paper is to discuss the issues connected with charges for re-use of public information, as laid down in the Directive 2003/98/EC of the European Parliament and of the Council of 17 November 2003 on the re-use of public sector information, and the Act on Access to Public Information. Polish legislation regulates such charges differently than many European states. It is a deliberate measure. When shaping this law, the legislative body adopted a free-of-charge rule for re-use of public information. However, charges for the re-use of public information may be levied by relevant bodies as an exception from this rule in situations when preparing the information in a manner specified in the application generates additional costs. In this regard, the legal solutions applied are in accordance with the stipulations of the Directive 2003/98/EC. Owing to a certain degree of freedom of choice offered in the Directive, Polish legislative body adopted a solution which is more beneficial from the perspective of entities using the public information. What is less satisfactory, however, is the regulation of the rules applied to the charges in question. The adopted solutions will give rise to discrepancies in the application of law.